2006
DOI: 10.1152/ajprenal.00361.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of NH2 and COOH termini in targeting, stability, and activity of sodium bicarbonate cotransporter 1

Abstract: Sodium bicarbonate cotransporter 1 (NBC1) mediates 80% of bicarbonate reabsorption by the kidney, but the molecular determinants for activity, targeting, and cell membrane stability are poorly understood. We generated truncation mutants involving the entire NH2 (⌬N424) or the entire COOH (⌬C92) terminus and examined the effects of these truncations on targeting, cell membrane stability, and NBC1 activity. ⌬N424 and ⌬C92 targeted to the plasma membrane of HEK293 cells or to the basolateral membrane of opossum k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Espiritu et al (97) demonstrated that deletion mutants lacking the cytoplasmic N- or C-terminal domains showed reduced basolateral membrane expression in opossum kidney OK cells. A recent report by Soleimani’s group shows that Asp 405 and Asp 416 in the N-terminal domain of NBCe1 are critical for protein expression in plasma membranes (190).…”
Section: The Postcloning Eramentioning
confidence: 99%
“…Espiritu et al (97) demonstrated that deletion mutants lacking the cytoplasmic N- or C-terminal domains showed reduced basolateral membrane expression in opossum kidney OK cells. A recent report by Soleimani’s group shows that Asp 405 and Asp 416 in the N-terminal domain of NBCe1 are critical for protein expression in plasma membranes (190).…”
Section: The Postcloning Eramentioning
confidence: 99%
“…Interestingly, mice with the disrupted NBCe1 gene showed metabolic acidosis (15), supporting both the clinical and in vitro observations mentioned above. The role of NH 2 -terminal of NBCe1A in its targeting, stability, and activity was previously examined in HEK293 cells and opossum kidney (OK) cells (12). In these studies, using an NH 2 terminus truncated mutant of NBCe1 (⌬N424), the importance of this region in NBCe1 targeting to the plasma membrane and functional activity was clearly demonstrated (12).…”
Section: Discussionmentioning
confidence: 99%
“…The role of NH 2 -terminal of NBCe1A in its targeting, stability, and activity was previously examined in HEK293 cells and opossum kidney (OK) cells (12). In these studies, using an NH 2 terminus truncated mutant of NBCe1 (⌬N424), the importance of this region in NBCe1 targeting to the plasma membrane and functional activity was clearly demonstrated (12). However, the scope of these data was limited in that it did not identify the specific motifs and amino acid residues that may play a role in the targeting of NBCe1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations